The contribution of low affinity transport mechanisms to serotonin clearance in synaptosomes - Hagan, Catherine E. (2011)
Although many studies assert that the serotonin (5-HT) transporter (SERT) is the predominant mechanism controlling extracellular 5-HT concentrations, accumulating evidence suggests that low affinity, high capacity transport mechanisms may contribute more to 5-HT clearance than previously thought. The goal of this study was to quantify the contributions of SERT relative to other mechanisms in clearing extracellular 5-HT concentrations ranging from 50 nM to 1 μM in synaptosomes prepared from wild-type and SERT knockout mice using rotating disk electrode voltammetry. SERT inhibitors combined with decynium-22 (D-22), a blocker of several low affinity transporters, blocked all uptake of 5-HT into synaptosomes. We found that SERT is responsible for the majority of synaptosomal uptake only at relatively low 5-HT concentrations, but comprises a diminishing proportion of 5-HT clearance when extracellular 5-HT increases above 100 nM. The effect of D-22 was similar in wildtype and SERT knockout synaptosomes. Thus, there was no evidence of upregulation of low-affinity mechanisms in knockout mice across the concentrations of 5-HT tested. These are surprising results, in light of the prevailing view that SERT is the primary uptake mechanism for extracellular 5-HT at physiological concentrations. We conclude that non-SERT mediated 5-HT uptake is substantial even at modest 5-HT concentrations. These findings, in conjunction with other studies, have important implications for understanding serotonergic disorders and may explain the variable efficacy and stability of patients’ responses to antidepressants, such as the selective serotonin reuptake inhibitors.